The Role of Trust and Engagement in Organizational Citizenship Behavior of Chemical Manufacturing Industry in Indonesia - Uli Wildan Nuryanto; Ika Pratiwi (Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
Although research on the relationship between trust and engagement with organizational citizenship behavior (OCB) has been extensively explored, the connection between these variables in the context of the chemical industry remains underexplored. The aim of this study is to examine the influence of trust on OCB, the impact of engagement on OCB, and the combined effects of trust and engagement on OCB in the Chemical Manufacturing Sector in Indonesia. This research employs a quantitative associative approach. The sample comprises 249 employees from manufacturing companies in the city of Cilegon, Indonesia, selected through proportional stratified random sampling techniques. The data analysis technique employed is multiple linear regression analysis using SPSS version 26. The findings of this study reveal that trust has a significant positive influence on OCB, engagement has a significant positive impact on OCB, and both trust and engagement collectively exert a significant positive influence on OCB in the Chemical Manufacturing Sector in Indonesia. The results of this research contribute to providing insights for chemical manufacturing companies in Indonesia to enhance the quality of their employees in achieving OCB principles.